Religious minorities, integration and the state = État, minorités religieuses et intégration - Jablonka, Ivan; Jaspert, Nikolas; Schreiber, Jean-Philippe; Tolan, John Victor (Brepols, 2016)
Judaism, Christianity and Islam have coexisted in Europe for over 1300 years. The three monotheistic faiths differ in demography, in the moment of their arrival on the continent and in the unequal relations they maintain with power: Christianity was chosen by a large number of inhabitants and became — in spite of important differences according to place and time —a religion of state. The organization of the continent into states and the divisions within Christianity often placed minorities in an unstable and at times painful situation. This partially explains the fight against "heresies", the wars of religions, the expulsion of Jews from several European kingdoms (as well as the expulsion of Muslims from Sicily and the Iberian peninsula), the "Jewish question" in the 19th century up until the Holocaust. Since the 20th century, the debates concerning Islam and concerning public expression of religion are shaped in part by this past. The 13 studies gathered in this volume explore the ways in which states have treated their religious minorities. We study various policies — repression, supervision, integration, tolerance, secularization, indifference — as well as the many ways in which minorities have accommodated the majority’s demands. The relation is by no means one-sided: on the contrary, state policies have created resistance, negotiation (on the legal, political, and cultural fronts) or compromise. Through these precise and original examples, we can see how the protagonists (states, religious institutions, the elite, the faithful) interact, try to convince or influence each other in order to transform practices, invent and implement common norms and grounds, all the while knowing the confessional dimension of "religious" majority and minority does not fully embrace the identity of each citizen in full